Strategic cross-fund subsidization of China’s mutual fund families. - Shao, Tiannu. (2012)
This paper examines the cross-fund subsidization strategies of China’s mutual fund families by investigating whether the mutual fund families boost the performance of high- performing funds at the expense of the low- performing members in order to increase the overall family profit. I find that the performance differences between the Net-of-Style Return of high performed funds and low performed funds are significantly greater if the pairs of funds are in the same family. These effects are independent of which set of funds is outperforming in terms of the investment style. This strategy is more prevalent in China when the investment styles of the low funds are outperforming. Moreover, the level of cross-fund subsidization is also related to family characteristics, including family age, family size, the number of funds possessed, and the size heterogeneity of the families’ member funds.